Computer propaganda is a new trend in communication technologies - Zhanpeissova К.Д.; Eralina Ж.Е. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2023)
The article analyzes in detail the activity of one of the communication technologies – computer propaganda. As technology develops, the types and forms of communication technologies used in political and social processes change. The article presents a comparative analysis of the features of modern computer propaganda and traditional propaganda, based on foreign research works. The work of political bots in social networks that implement propaganda has also been studied. It provides tan analysis of the rate of actions of computer propaganda in political events. Also, it explains the problems of the automatic implementation of promotion algorithms in social networks, such as Twitter and Facebook.